RETRACTED: Comparative assessment of the spread of respiratory diseases of occupational etiology in regions with a highly developed mining industry - Akhmedova Dilafruz; Azimova Sevara (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001